Impacts on the growing and adult skeleton of different genetically-achieved RANKL activity levels, consequences on the response to zoledronic acid (2019)
ABSTRACT: Bone is a dynamic tissue with constant adaptative physiological changes in its homeostasis through life called bone modeling and remodeling. These processes enable to achieve a balance between bone formation and bone resorption at any particular age. These processes involve the activity of distinct types of cells namely chondroblasts, osteocytes, osteoblasts, bone lining cells and osteoclasts. The role of the osteoclasts has been deeply analyzed in endochondral ossification during development and growth, and in adulthood throughout bone remodeling. Osteoclast differentiation requires two essential factors named macrophage colony stimulating factor (M-CSF), acting on its receptor c-FMS, and receptor activator of nuclear factor-κB ligand (RANKL), acting on its main receptor RANK which binding is modulated by the decoy receptor osteoprotegerin (OPG). M-CSF is involved in the osteoclastogenesis process mainly by promoting the proliferation and survival of osteoclast precursors. RANKL functions as the primary factor driving differentiation of osteoclasts precursors into ostéoclasts, as well as in their maturation and activity. Any imbalances between bone formation and resorption secondary to osteoclasts alterations lead to pathologies that could appear either in childhood or adulthood. Those pathologies are known as osteopetrotic and osteolytic diseases. Osteopetrotic disease group is related to a greater bone apposition, resulting in a bone mass increased, mainly due to osteoclasts dysfunction or absence. The osteolytic disease group, on the contrary, is related to an increase in bone turnover associated to an increase in osteoclasts number or/and activity. Osteolytic diseases are so characterized by a negative balance between bone formation and resorption. Osteolytic diseases generate a low bone density and a deterioration of bone microarchitecture, leading towards a weak bone phenotype and a higher fracture risk. These pathologies have different etiologies and affect both children and adults. Osteolytic diseases affecting children include an inherited group of rare disorders and can be divided into two types, early and late, depending on the timing of the osteoporotic onset. Early-onset osteoporosis is related to genetic mutations and appears soon after birth. Late-onset forms are related with hypercalcemic disorders (hyperparathyroidism, vitamin D-related causes, malignancy, medications, endocrine disorders, genetic disorders, and miscellaneous causes). In adults, osteolytic diseases include primary (or age-related) osteoporosis that is the most common form with two types. The first is associated with estrogen deficiency at menopause and the second related to long-term remodeling inefficiency. Secondary osteoporosis could appear in the context of endocrine, reproductive, gastrointestinal and nutritional disorders, following treatments with drugs like glucocorticoids and anti-convulsants, in the case of Paget disease, in the presence of malignant primary bone tumors or associated with bone metastases of other cancers as breast and prostate cancers.